2009
DOI: 10.1088/0004-637x/695/1/707
|View full text |Cite
|
Sign up to set email alerts
|

A Multiwavelength Study of the High Surface Brightness Hot Spot in PKS 1421–490

Abstract: Long Baseline Array imaging of the z = 0.663 broadline radio galaxy PKS 1421−490 reveals a 400 pc diameter high surface brightness hot spot at a projected distance of ∼40 kpc from the active galactic nucleus. The isotropic X-ray luminosity of the hot spot, L 2-10 keV = 3 × 10 44 ergs s −1 , is comparable to the isotropic X-ray luminosity of the entire X-ray jet of PKS 0637−752, and the peak radio surface brightness is hundreds of times greater than that of the brightest hot spot in Cygnus A. We model the radio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 61 publications
5
56
0
Order By: Relevance
“…Specifically, the minimum Lorentz factor of this electron energy distribution is related to the luminosity as L rad ∝ γ min s−2 (Equation 8 of . The minimum Lorentz factor in the hotspot has been estimated by other authors for selected radio sources including: Cygnus A (McKean et al 2016), PKS 1421-490 (Godfrey et al 2009), 3C123, 3C196 and 3C295 (Hardcastle 2001). These hotspot Lorentz factor estimates are mostly in the order of a few hundred although these estimates are quite uncertain due to the confounding effects of free-free and synchrotron selfabsorption.…”
Section: Minimum Electron Lorentz Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the minimum Lorentz factor of this electron energy distribution is related to the luminosity as L rad ∝ γ min s−2 (Equation 8 of . The minimum Lorentz factor in the hotspot has been estimated by other authors for selected radio sources including: Cygnus A (McKean et al 2016), PKS 1421-490 (Godfrey et al 2009), 3C123, 3C196 and 3C295 (Hardcastle 2001). These hotspot Lorentz factor estimates are mostly in the order of a few hundred although these estimates are quite uncertain due to the confounding effects of free-free and synchrotron selfabsorption.…”
Section: Minimum Electron Lorentz Factormentioning
confidence: 99%
“…The minimum Lorentz factor of the electron energy distribution at the hotspot reduces accordingly as the electrons propagate throughout the lobe; the Lorentz factor in the lobe does not need to be explicitly measured. Following Godfrey et al (2009) we assume a typical hotspot minimum Lorentz factor of γ min = 500 for the sources in our sample. Systematic errors in AGN intrinsic parameter estimates are derived for realistic Lorentz factors in the range γ min = 100-1000, yielding a 0.19 dex uncertainty in jet power estimates, 0.06 dex in source ages, and 0.01 dex in equipartition factors.…”
Section: Minimum Electron Lorentz Factormentioning
confidence: 99%
“…The existence of protons in the jet is supported by several observations of the AGN jets (see Sikora 2011 for a review): (1) the detection of circular polarization and Faraday rotation of the radio core. This is because the electron-positron plasma cannot generate any polarization (Park & Blackman 2010); (2) the low-energy cutoff in the radio spectra (and also the electron energy distribution) of hotspots in radio-lobes, which is likely a consequence of dissipation of bulk kinetic energy in an electron-proton jet (Godfrey et al 2009). We mainly follow Spada et al (2001) to calculate the radiation from the jet 1 .…”
Section: The Jet Modelmentioning
confidence: 99%
“…For the same hotspot, the authors derived a low magnetic field strength, 21.5 μG. Godfrey et al (2009) studied the radio and X-ray emission from the hotspots in PKS 1421−490. Fitting the radio and optical fluxes with a one-zone synchrotron self-Compton emission, they concluded that the minimum Lorentz factor is about 650, or higher if beaming is important.…”
Section: Minimum Electron Lorentz Factor For the Hotspotsmentioning
confidence: 99%